Service uptake and performance of the prevention of mother-to-child transmission (PMTCT) programme in Ibadan, Nigeria (2010)
The Prevention of Mother to Child Transmission (PMTCT) programme in the University College Hospital (UCH), Ibadan has been in existence for more than five years and has scaled up to other sites. The study evaluated the service uptake and performance of the programme using national key indicators. Antenatal and delivery records of women enrolled between July 2002 and June 2007 were reviewed. A total of 51952 women attended first antenatal visits and received HIV pre-test counselling. Of these, 51614 (99.5%) accepted HIV test and 49134 (95.2%) returned for their results. Out of the tested patients, 2152 (4.2%) were identified to be HIV positive. Partners of positive patients accepting HIV testing were 361 (16.7%) with 87 (18.6%) testing positive. There were a total of 942 deliveries out of which 39.2% of the mothers and 95.2% of the babies respectively received ARV prophylaxis. In all, 85.8% (788/918) of the mothers opted for formula as the method of infant feeding. Out of the 303 babies eligible for ELISA testing, 68.3% reported for the test and 17 (8.7%) tested positive. There has been progress in the programme, reflected in the increase in the number of new clients accessing the PMTCT service. However, partner testing and follow up of mother-infant pairs remain formidable challenges that deserve special attention.